Broken Harmony : Shakespeare and the Politics of Music - Ortiz, Joseph M., 1972- (Book collections on Project MUSE., 2011)
The author takes on the important topic of music as a scripted event in Shakespeare's plays. To the philosophical and practical aspects of early modern music he adds a politics of music that gets to the heart of religious controversy in the period between Catholic and Protestant, high church and low church.